Atypical rabies encephalitis in a six-year-old boy: clinical, radiological, and laboratory findings. (July 2015) - Karande, Sunil; Muranjan, Mamta; Mani, Reeta Subramaniam; Anand, Ashwini Manoor; Amoghimath, Raghavendraswami; Sankhe, Shilpa; Belludi, Ashwin Yajaman; Madhusudana, Shampur Narayan
Highlights: We report the case of a rabies survivor from India with atypical manifestations. The standard post-exposure prophylaxis protocol was not followed. Diagnosis was based on high titres of neutralizing antibodies in the cerebrospinal fluid and serum. Summary: A 6-year-old boy from India developed an atypical form of rabies following a stray dog bite and as a consequence of not receiving the standard World Health Organization recommended post-exposure prophylaxis for category III wounds. Serial rising rabies virus neutralizing antibody titres in serum and cerebrospinal fluid by rapid fluorescent focus inhibition test helped confirm the diagnosis of rabies. The child has survived for 4 months since the onset of illness, albeit with neurological sequelae.